Implementasi BERT dan SNA dalam Sistem Tanya Jawab untuk Survei Demam Berdarah Dengue - Nadifah, Rofiatun; Syaifullah, Rindra; Almaasah Zatri, Nasywaa; Putri Permata, Regita (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2025)
As a global public health challenge, Dengue Hemorrhagic Fever (DHF) necessitates an analysis of public understanding and perception. For controlling the spread of DHF, survey data is instrumental in uncovering these perceptions. This study was conducted to perform an in-depth analysis of the public's understanding of DHF by analyzing textual responses from surveys. The analyzed data consists of answers from 33 respondents to five key questions concerning the definition, symptoms, causes, transmission, and prevention of DHF. The methods used were semantic similarity analysis with a pre-trained BERT model, cosine similarity calculation, and Social Network Analysis (SNA) to identify key respondents as opinion leaders and to map the patterns of understanding dissemination. In this model, a highly consistent level of understanding was obtained, with an F1-Score for the "Very Similar" category reaching 0.94 and a highest cosine similarity value of 0.995.